Development and Validation of the Homeostasis Concept Inventory - McFarland, Jenny L; Price, Rebecca M; Wenderoth, Mary Pat; Martinková, Patrícia; Cliff, William; Michael, Joel; Modell, Harold; Wright, Ann (CBE life sciences education, 2017)
We present the Homeostasis Concept Inventory (HCI), a 20-item multiple-choice instrument that assesses how well undergraduates understand this critical physiological concept. We used an iterative process to develop a set of questions based on elements in the Homeostasis Concept Framework. This process involved faculty experts and undergraduate students from associate's colleges, primarily undergraduate institutions, regional and research-intensive universities, and professional schools. Statistical results provided strong evidence for the validity and reliability of the HCI. We found that graduate students performed better than undergraduates, biology majors performed better than nonmajors, and students performed better after receiving instruction about homeostasis. We used differential item analysis to assess whether students from different genders, races/ethnicities, and English language status performed differently on individual items of the HCI. We found no evidence of differential item functioning, suggesting that the items do not incorporate cultural or gender biases that would impact students' performance on the test. Instructors can use the HCI to guide their teaching and student learning of homeostasis, a core concept of physiology.
Keywords: rozvoj plánování; Faculty; Universities; průzkumy a dotazníky; Reproducibility of Results; studenti; akademický sbor; Educational Measurement; Humans; Students; Homeostasis; homeostáza; reprodukovatelnost výsledků; univerzity; výuka - hodnocení; Program Development; lidé; Surveys and Questionnaires